2010
DOI: 10.1152/jn.00679.2010
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Dynamics of Rhythmic Spinal Interneurons Measured With Two-Photon Calcium Imaging and Coherence Analysis

Abstract: .2010. In rhythmic neural circuits, a neuron often fires action potentials with a constant phase to the rhythm, a timing relationship that can be functionally significant. To characterize these phase preferences in a large-scale, cell type-specific manner, we adapted multitaper coherence analysis for two-photon calcium imaging. Analysis of simulated data showed that coherence is a simple and robust measure of rhythmicity for calcium imaging data. When applied to the neonatal mouse hindlimb spinal locomotor net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 55 publications
2
24
1
Order By: Relevance
“…In the mouse spinal cord, the rhythmically activeV2a interneurons appear to be recruited more like motoneurons: virtually all increase their activity monotonically with cycle frequency. We have not observed any significant relation between the neuronal location and V2a firing properties during fictive locomotion; Kwan et al (2010) used calcium imaging techniques to monitor V2a activity during fictive locomotion, and did not find any spatial clustering of rhythmically active vs. tonic V2a interneurons 44 . Some V2a neurons start firing at lower frequencies, and increase their activity (action potentials per cycle) as the locomotor speed accelerates (Figs.3 and 6).…”
Section: Discussioncontrasting
confidence: 61%
“…In the mouse spinal cord, the rhythmically activeV2a interneurons appear to be recruited more like motoneurons: virtually all increase their activity monotonically with cycle frequency. We have not observed any significant relation between the neuronal location and V2a firing properties during fictive locomotion; Kwan et al (2010) used calcium imaging techniques to monitor V2a activity during fictive locomotion, and did not find any spatial clustering of rhythmically active vs. tonic V2a interneurons 44 . Some V2a neurons start firing at lower frequencies, and increase their activity (action potentials per cycle) as the locomotor speed accelerates (Figs.3 and 6).…”
Section: Discussioncontrasting
confidence: 61%
“…Second, in contrast to local dye application methods used by others [31], [32], all networks from T13 to L5 were uniformly labeled by bath-application of the membrane permeant indicator. Thus, the observation of locomotor-related activity concentrated at L1 likely indicates functional specialization of networks in this region.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6), we find that although mixed, flexor interneurons predominate rostrally, and extensor interneurons caudally. This relates to in vitro locomotion results of a mixture of preferred interneuronal firing phases in each segment, but more often in phase with the segment output, flexor in L2, and extensor in L5 (Tresch and Kiehn 1999;Cheng et al 2002;Kwan et al 2010;Dougherty and Kiehn 2010;Zhong et al 2010, but see Auyong et al 2011;Antri et al 2011;Hinckley and Pfaff 2013, who found no correlation between firing phase and rostrocaudal location). The overlap of the preferred zones of activation of different synergies in Figs.…”
Section: Topography Of Synergiesmentioning
confidence: 99%